Direct aspiration through a balloon guide catheter can augment vessel wall injury. Issue 6 (26th August 2021) - Inoue, Hiroyasu; Yamada, Kentaro; Oomura, Masahiro; Naiki‐Ito, Aya; Matsukawa, Noriyuki
Abstract: We report a 75‐year‐old woman with extracranial internal carotid artery occlusion treated with neurointervention. The patient presented with tandem lesions for which mechanical thrombectomy was performed. Retrieval of massive white clots and endothelial tissue by forceful manual aspiration via a balloon guiding catheter after angioplasty can be indicative of augmentation of vessel wall injury.